Efficacy and Safety of Letibotulinumtoxin A in the Treatment of Glabellar Lines: A Randomized, Double-Blind, Multicenter, Placebo-Controlled Phase 3 Study. (2nd February 2022) - Mueller, Daniel S; Prinz, Valentina; Adelglass, Jeffrey; Cox, Sue Ellen; Gold, Michael H; Kaufman-Janette, Joely; Nestor, Mark S; Taylor, Susan; Frank, Konstantin
Abstract: Background: Letibotulinumtoxin A (Hugel, Inc., Chuncheon, Republic of Korea and CROMA Pharma, Leobendorf, Austria) is a newly manufactured neurotoxin derived from Clostridium botulinum strain CBFC26. Objectives: The aim of this study was to assess the efficacy and safety of letibotulinumtoxin A in reducing glabellar line severity (GLS) and to evaluate long-term safety and efficacy following repeated injections. Methods: In this prospective, randomized, parallel-group, double-blind, multicentre, placebo-controlled Phase III clinical trial, 355 subjects with moderate to severe glabella frown lines received injections of 20 U of letibotulinumtoxin A or placebo. GLS, onset and duration of effect, time to retreatment, and adverse events were evaluated. Response to treatment was defined as a GLS score of 0 or 1 (assessed by the subject and the investigator) and an improvement at Week 4 of ≥2 points in GLS score relative to baseline. Results: At 4 weeks, 78.6% of the active treatment subjects were responders based on the investigator's assessment and 68.8% based on the subject's assessment, resulting in a composite responder rate of 64.7% for the active treatment group, whereas the corresponding rate was 0.0% in the placebo group ( P  < 0.001). Subjects noted a substantial improvement in GL severity as early as Day 2, with the median time to onset of effect being 3 days. The mean [standard deviation] time until first retreatment for the letibotulinumtoxin A group was 127.26 [65.6] days. Letibotulinumtoxin A was well tolerated. Conclusions: Letibotulinumtoxin A demonstrates high efficacy and a convincing safety profile in the treatment of glabellar lines. Level of Evidence: 2: